Comparison of oral midazolam versus oral dexmedetomidine for ease of induction and prevention of emergence delirium in pediatric ENT surgeries under sevoflurane anesthesia: a randomized controlled study - Panigrahi, Abinash; Fotedar, Kamal Kumar; Mehta, Punit; Sachdeva, Sanjay; Singh, Pooja (International Journal of Research in Medical Sciences, 2025)
Background: Emergence delirium (ED) is a common and distressing complication in pediatric patients following sevoflurane anesthesia. Preoperative anxiety, rapid anaesthetic emergence and postoperative pain contribute to ED. Midazolam is widely used for premedication but has variable efficacy in preventing ED. Dexmedetomidine, a selective alpha-2 agonist, offers sedative and analgesic properties with minimal respiratory depression. This study compared the efficacy of oral midazolam versus oral dexmedetomidine for ease of induction and prevention of ED in children undergoing ENT surgeries under sevoflurane anesthesia. Methods: In this prospective, randomized, single-blinded trial, 100 children aged 2–12 years (ASA I–II) scheduled for elective ENT surgeries were assigned to receive either oral midazolam 0.5 mg/kg (Group M) or oral dexmedetomidine 2 µg/kg (Group D) 45 minutes before induction. Preoperative sedation, ease of parental separation, mask acceptance, hemodynamic stability, incidence of ED (assessed using the Pediatric Anesthesia Emergence Delirium (PAED) scale) and recovery profiles were recorded. Results: Baseline demographics were comparable between groups. Group D demonstrated significantly better preoperative sedation (RSS 3.6 vs 2.8, p<0.001), easier parental separation (90% vs 74%, p=0.03) and superior mask acceptance (88% vs 70%, p=0.02). The incidence of ED was significantly lower in Group D (8%) compared to Group M (26%, p=0.01). PACU discharge was earlier in Group D (36.5 vs 42.8 minutes, p=0.04). Hemodynamic parameters remained stable in both groups without significant adverse events. Conclusions: Oral dexmedetomidine provides superior preoperative sedation, smoother induction and significantly reduces emergence delirium compared to oral midazolam in children undergoing ENT surgeries under sevoflurane anesthesia. Dexmedetomidine may be considered a preferred premedication option in pediatric anesthesia practice.